Time to first antenatal care visit and its predictors among women in Kenya: Weibull gamma shared frailty model (based on the recent 2022 KDHS data) - Bizunesh Fantahun Kase; Beminate Lemma Seifu; Kusse Urmale Mare; Abdu Hailu Shibeshi; Hiwot Altaye Asebe; Kebede Gemeda; Zufan Alamrie Asmare; Yordanos Sisay Asgedom; Bezawit Melak Fente; Afework Alemu Lombebo; Tsion Mulat Tebeje (BMC Pregnancy and Childbirth)
Abstract Background The first trimester of pregnancy is critical for fetal development, making early antenatal care visits essential for timely check-ups and managing potential complications. However, delayed antenatal care initiation remains a public health challenge in sub-Saharan Africa, including Kenya. Therefore, this study aimed to assess and provide up-to-date information on time to first antenatal care visit and its predictors among women in Kenya, using data from the most recent 2022 Kenya Demographic and Health Survey (KDHS). Methods This community-based cross-sectional study analyzed data from 19,530 birth histories in the 2022 Kenya Demographic and Health Survey (KDHS). The primary outcome was the timing of the first antenatal care (ANC) visit, classified as timely if it occurred in the first trimester. Shared frailty survival models were used to account for the hierarchical data structure and unobserved heterogeneity, with the Weibull gamma model identified as the best fit based on Information Criteria (AIC), and Bayesian Information Criteria (BIC). Variables with p < 0.2 entered multivariable analysis, and results were reported as Adjusted Hazard Ratios (AHR) with 95% Confidence Intervals (CI) using the Weibull gamma model. Results The study found that the median time for the first antenatal care (ANC) visit in Kenya was four months. Significant predictors of ANC timing included women’s age (35–49 years: AHR 0.83; 95% CI: 0.72–0.95), education level (higher: AHR 1.45; 95% CI: 1.17–1.78), media exposure (yes: AHR 1.21; 95% CI: 1.05–1.39), parity (four or more children: AHR 0.81; 95% CI: 0.72–0.91), wealth status (richest: AHR 2.00; 95% CI: 1.63–2.43), desire for more children (did not want more: AHR 0.64; 95% CI: 0.54–0.77), residence (rural: AHR 1.22; 95% CI: 1.07–1.39), and religion (Islam: AHR 0.76; 95% CI: 0.64–0.89). Conclusion The median time for the first ANC visit exceeds the World Health Organization’s recommendation of initiating care within the first trimester. These findings underscore the need for targeted interventions to promote timely ANC, especially among women with limited media exposure, high parity, lower socioeconomic status, and specific religious followers.